PERSEPSI MAHASISWA FAKULTAS EKONOMI MENGENAI ETIKA PENGGELAPAN PAJAK - Dhea Alit; Meylan Kambuaya; Pascalina V. S Sesa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2021)
This study aims to analyze the effect of justice, taxation system, discrimination and understanding of taxation on economic students' perceptions of the ethics of tax avoidance. The population in this study were students at the state and private Faculty of Economics campuses. The sample in this study was determined using purposive sampling technique, data collection was carried out by distributing questionnaires. The research analysis method used is multiple linear regression. Based on the results of the analysis, it shows that justice has a negative and insignificant effect on students' perceptions of tax avoidance ethics, the taxation system has a negative and insignificant effect on students' perceptions of tax avoidance ethics, discrimination has a positive and insignificant effect on students' perceptions of tax avoidance ethics and has a significant effect on students' perceptions of the ethics of tax avoidance and negative understanding of taxation. and not significant to students' perceptions of the ethics of tax avoidance. The most dominant variable influencing students' perceptions of the ethics of tax avoidance is discrimination because it has a standard value of 0.900 beta coefficient.